THE DEVELOPMENT OF ANDROID- BASED MIDWIFERY LAW APPLICATIONS IN THE IMPLEMENTATION OF INDEPENDENT MIDWIFE PRACTICES - nuryuniarti, rissa; Nurmahmudah, Endah; Badrudin, Ubad; Purwanto, Suci Dewanti (Universitas Galuh, 2024)
Problems in health services are closely related to the midwifery Profession, in providing health services neglicences or malpractice can occur. some problems arises when a midwife Is negligent in carrying out health services and does not comply with her authority. This research using normative development Research, this research is to create Android-based Midwifery Law application software as a reference that can be easily applied in carrying out independent midwifery practices that apply in accordance with the Law.Number 17 of 2023 concerning Health, onArticle 454 of Law 17/2023 regulates 11 laws that are revoked and declared invalid. The results of this research conclude that the Android-based Midwifery Law application can be installed, so that the Android-based Midwifery Law application becomes an electronic means for understanding and searching for applicable midwifery regulations. All statutory regulations which constitute the implementing regulations of the Midwifery Law are declared to still be valid as long as they do not conflict with the provisions of the Health Law, namely, Minister of Health Regulation No. 28 of 2017 concerning Licensing and Implementation of Midwife Practice,Minister of Health Decree 320 of 2020 concerning Midwifery Professional Standards,Minister of Health Decree 1261 of 2022 concerning Work Competency Standards in the Field of midwifery.